PENGARUH BYSTANDER, REPORTING CHANNEL ADMINISTRATION, PERCEIVED PERSONAL RESPONSIBILLITY DAN PERCEIVED SERIOUSNESS TERHADAP WHISTLEBLOWING INTENTION (Studi Empiris pada Perusahaan Perbankan yang berada di kota Pekanbaru) - Azka Amila; Surya Adri Satriawan Raja; Zarefar Arumega (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This studied examines the effect of bystander, reporting channeladministration, perceived personal responsibillity and perceived seriousness onwhistleblowing intention. The sample of this study is 28 of banking companies thatlisted in Bursa Efek Indonesia (BEI) which branch in the city of Pekanbaru. This researchappromited quantitative. Analytical techniques used to perform the hypothesis testing ispurposive sampling. Data are analyzed using multiple regression method with usingSPSS (Statistical Product and Service Solution) 17 version. The results showedvariable bystander not affected whistleblowing intention with significant value0,106 so the conclution H1 accepted. Reporting channel administration positiveaffected whistleblowing intention with significant 0,003 so the conclution H2accepted. Perceived personal responsibillity not affected whistleblowing intentionwith significant 0,656 so the conclution H3 accepted. Perceived seriousnessnegative affected whistleblowing intention with significance value of 0.013 and H4accepted. The results of this study support previous research conducted by Gao, etal (2014) and Ayers (2005).Keyword: Bystander, Reporting Channel Administration, Perceived PersonalResponsibillity, Perceived Seriousness and WhistleblowingIntention.